EVALUASI BAHAN AJAR MATAKULIAH KYOUJUHOU : “PERAN GURU DAN METODE PENGAJARAN BAHASA JEPANG” - Dwi Astuti Retno Lestari; Nia Setiawati; Tia Ristiawati (Universitas Negeri Jakarta, 2024)
The Japanese Language Education Study Program at State University of Jakarta has designated Japanese language teachers as its graduate profile. To achieve the profile, a series of courses have been prepared, one of which is Nihongo Kyoujuhou that equips students with Japanese language teaching methodology. However, observations of pre-service teaching practices and evaluation of learning outcomes show that students’ teaching skills are still need to be improved. There are some causal factors, one of which is the teaching materials used. Starting from the 2019/2020 academic year, Nihongo Kyoujuhou course use